Combinatorics and finite fields : difference sets, polynomials, pseudorandomness and applications - Schmidt, Kai-Uwe; Winterhof, Arne (De Gruyter, 2019)
Combinatorics and finite fields are of great importance in modern applications such as in the analysis of algorithms, in information and communication theory, and in signal processing and coding theory. This book contains survey articles on topics such as difference sets, polynomials, and pseudorandomness.- Resumé vydavatel
Keywords: kombinatorika; Galoisova teorie; abstraktní algebra; combinatorics; Galois theory; abstract algebra; elektronické knihy; sborníky; electronic books; papers of several atuhors